Macroeconomic policy and financial sector stability in St. Kitts and Nevis ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Assesses the public sector macroeconomic policy in light of the financial sector and the stability deriving from the macroeconomic policy on the financial sector.
Keywords: MONETARY POLICY